Probability - Edward Arnold; Rowntree Derek (1984)
A tool used by all kinds of specialists from business men to meteorologists and an excellent first course in the ideas of probability. Preface, Simple Probabilities, Choice and Change, Judging by Experience, Gambling and Probability and Belief, Combined Probabilities, Total Probability, Joint Probability, Using Both Probability Rules Together, Review, Combinations and Permutations, Combining and Permuting, Formulae for Permutations, From Permutations to Combinations, Probability by Combinations, Probability Again, Experiments in Probability and Sampling, Combinations and the Binomial Distribution, Co-Efficiency from Combinations, Review.